Effects of Xiaoyaosan on the Hippocampal Gene Expression Profile in Rats Subjected to Chronic Immobilization Stress - Li, Xiao-Hong; Zhou, Xue-Ming; Li, Xiao-Juan; Liu, Yue-Yun; Liu, Qun; Guo, Xiao-Ling; Yang, Li-Qiang; Chen, Jia-Xu (Frontiers in Psychiatry, 2019)
Objective: This study examined the effect of Xiaoyaosan and its anti-stress mechanism in rats subjected to chronic immobilization stress at the whole genome level. Methods: Rat whole genome expression chips (Illumina) were used to detect differences in hippocampal gene expression in rats from the control group (CN group), model group (M group) and Xiaoyaosan group (XYS group) that were subjected to chronic immobilization stress.The Gene Ontology terms and signalling pathways that were altered in the hippocampus gene expression profile were analysed. The network regulating the transcription of the differentially expressed genes was also established. To verify the results from the gene chips, real-time quantitative polymerase chain reaction was used to determine the expression of the GABRA1, FADD, CRHR2, and CDK6 genes in hippocampal tissues. In situ hybridization (ISH) and immunohistochemistry were used to determine the expression of the GABRA1 and CRHR2 genes and proteins, respectively. Results: Compared with the CN group, 566 differentially expressed genes were identified in the M group. Compared with the M group, 544 differentially expressed genes were identified in the XYS group. In the M and XYS groups, multiple significantly upregulated or downregulated genes functioned in various biological processes. The cytokine receptor interaction pathway was significantly inhibited in the hippocampus of the model group. The actin cytoskeleton regulation pathway was significantly increased in the hippocampus of the XYS group. The inhibition of hippocampal cell growth was the core molecular event of network regulating the transcription of the differentially expressed genes in the model group. Promotion of the regeneration of hippocampal neurons was the core molecular event of the transcriptional regulatory network in the XYS group. The levels of the GABRA1, FADD, CRHR2 and CDK6 mRNAs and proteins were basically consistent with the results obtained from the gene chip. Conclusion: XYS may have the ability of resistance to stress, enhancement immunity and promotion nerve cell regeneration by regulating the expression of multiple genes in numerous pathways and repaired the stress-induced impairments in hippocampal structure and function by inducing cytoskeletal reorganization. These results may provide the possible target spots in the treatment of stress in rats with XYS.